Pengaruh Kemandirian Belajar Matematik Siswa Terhadap Kemampuan Berpikir Kreatif Matematis Siswa SMP - Fuji Sri Astuti; Tri Buana Bintang; Rizka Vita Utami; Padillah Akbar (Departement of Mathematics Education, 2020)
This research aims to analyze and in study about influence of mathematical by self regulated learning against the ability of mathematical creative thinking high school students. The methods used in this research is quantitative data with the correlational method. The population in this research is a high school student in the city of Karawang with sampels as many as 32 student that assigned by techniques purposif sampling at one high school in the city of Karawang. The instruments in this research is a test of the ability of mathematical creative thinking as much as 4 items and scale self regulated learning as much as 10 scale statements.